Maxillofacial surgery: maxillary osteosynthesis craneomaxillofacial CMS-titanium plates - Vérez-Fraguela, J. L.; Vallés, M. A. Vives (Veterinary and Comparative Orthopaedics and Traumatology, 2000)
A maxillary fracture is presented which we classified as Le Fort Type III. Treatment was by the application of two craniomaxillofacial CMS titanium plates placed intrabuccally and paramedially on both sides of the palatal suture.This technique was used as an alternative to the classical treatment using interdental wires or intermaxillary fixation.A clinical case was diagnosed with a craniofacial fracture caused from being bitten by another dog. This was successfully treated using CMS titanium plates. Many methods exist for maxillofacial fixation, from the cyanocrylates to interdental wires, etc. The indications for these plates are similar to other methods of fixation. Due to their small mass they are ideal for use in fragile bones with little soft tissue covering.
Keywords: Fractures; maxilla; canine